PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN DAN JOB RELEVANT INFORMATION TERHADAP KINERJA MANAJERIAL - Bonifasius Hamonangan Tambunan (Journal of Economic and Business, 2020)
The purpose of this study was to determine and analyze the effect of budgetary participation and job relevant information on managerial performance at PT. Taspen (Persero) Medan City. In this study, using a saturated sample of 31 people. The approach used is quantitative by processing the data obtained from the questionnaire after first being transformed into numeric data using a Likert scale. The data were processed using SPSS 23.0 software. The analysis used is multiple linear analysis. The research instrument test consisted of validity and reliability tests. The classical assumption test consists of normality test, heteroscedasticity test, multicollinearity test, and autocorrelation test. Hypothesis testing consists of f test (simultaneous test), t test (partial test) and determinant coefficient test (R2). The results showed that there was no partially significant influence of the budgetary participation variable on managerial performance. There is no partially significant influence of the job relevant information variable on managerial performance. Keywords: Budgetary Participation, Job Relevant Information and Managerial Performance